Evaluation of Gene Xpert as compared to conventional methods in diagnosis of Female Genital Tuberculosis. (December 2020) - Sharma, Jai B.; Dharmendra, Sona; Jain, Shefali; Sharma, S.K.; Singh, Urvashi B.; Soneja, Manish; Sinha, Sanjeev; Vanamail, P.
Abstract: To evaluate Gene Xpert for diagnosis of Female Genital Tuberculosis (FGTB) as compared to conventional methods. Study Design: It was a prospective study conducted over 167 cases of infertile female genital tuberculosis (FGTB) diagnosed on composite reference standard (CRS) (smear for AFB, histopathological evidence of epithelioid granuloma or definite or possible findings of tuberculosis on laparoscopy). All women underwent endometrial biopsy for AFB microscopy, culture, gene Xpert, PCR and histopathology) and laparoscopy and hysteroscopy for diagnosis and prognostication of disease. The results of Gene Xpert were compared with conventional methods in detection of FGTB. All patients were treated with 6 months course of rifampicin (R), isoniazid (H), pyrazinamide (Z) and ethambutol (E) (RHZE for 2 months, RHE for 4 months) using directly observed treatment short course strategy. Results: Mean age, parity, body mass index and history of contact was 28.3 years, 0.28, 22.9 Kg/m 2 and 38.92% respectively. Primary infertility was seen in 87.42% cases with mean duration of 2.42 years. Menstrual dysfunctions, abdominal or pelvic pain and lump were seen in 38.92%, 14.37% and 10.77% cases. Abnormal vaginal discharge and adnexal mass were seen in 28.14% and 13.17 % cases. On diagnostic laparoscopy, definite findings of tuberculosis (beaded tubes, tuebrcles and caseous nodules) were seen in 96 (57.48%) women while probable findings of tuberculosis (pelvic or abdominal adhesions, hydrosaplinx, tubo-ovarian mass, pyosalpinx) were seen in 81 (48.50%) women. On laboratory investigations, positive AFB on microscopy or culture was seen in 2.99% casess, PCR was positive in 47.90% gene Xpert was positive in 18.56% cases while epitheloid granuloma was seen on histopathology in 16 (9.58%) cases. Gene Xpert had sensitivity of 35.63%, specificity of 100%, positive predictive value of 100% and negative predictive value of 58.82% and diagnostic accuracy of 66.47% in the present study. Conclusion: Gene Xpert is a very useful test to rule in tuberculosis whereas when it is negative it is not a good test to rule out tuberculosis.